Mastery learning and deliberate practice: Do simulationists need clarification?. (December 2022) - Clapper, Timothy C.
Background: When the concepts of mastery learning and deliberate practice are applied in accordance with their intended meaning, they can be used to create robust learning opportunities that can ensure that more learners achieve and maintain higher standards of competency. With the rapid expansion of healthcare simulation over the past 10–15 years, these concepts are not always described accurately in the literature, leaving those considering the use of these practices vulnerable to inaccurate interpretation and application. Aim: The purpose of this article is to provide a much-needed clarification of mastery learning and deliberate practice for those conducting simulation-based education. This clarification includes defining background information on these two important concepts and suggestions for application. Conclusion: An accurate understanding of mastery learning and deliberate practice can ensure that going forward, we properly design interventions, systems, and research protocols that can inform us about what works best for our learners.